Karel Holle dan Modernisasi Pengetahuan Pertanian Sunda Abad XIX: Potensinya sebagai Sumber Belajar Sejarah Berwawasan Lingkungan - Farrel Eka Prasetya; Ronal Ridhoi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This article highlights the role of Karel Frederik Holle, a Dutch figure who worked in the Sundanese Land in the 19th century. Holle played a role in the development of agricultural techniques. Through historical methods, by conducting in-depth readings of archival sources and Holle's writings, this article attempts to examine Holle's contribution in introducing a sustainable agricultural system, including soil conservation techniques and adaptive planting patterns based on collaboration within both, Western and local knowledge. In addition, this article examines the potential for utilizing Holle's work as a source of historical learning that not only enriches students' insights into the past event, but also enhancing environmental awareness. The results of this articleshows that Holle gave so much contribution on agriculture technological knowledge. He also had an ecological vision that are relevant to the context of current history learning which offers a new historiographic theme, environmental history learning. Thus, this figure can be used as an entry point for history education that concern on sustainable environmental values.